Strengthening women’s psychosocial support through psychoeducation in the Former Argorejo Localisation Area - Pradipta Christy Pratiwi; Lukki Lukitawati; Moh. Farizqo Irvan; Chamilul Hikam Al Karim; Fikrotul Hanifah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The Argorejo karaoke district has become a popular destination for night-time leisure activities in Semarang. A study was conducted in collaboration with the Argorejo Karaoke Association (PAKAR). It was determined that specific programmes, including those utilising psychological principles, is necessary. The challenges experienced by these individuals frequently pertain to a lack of support from their social networks, profound emotional distress, and an inability to effectively cope with adversity. The psychoeducation approach was employed in a study involving 49 females who were employed as lady companions. Initially, the participants were provided with psychosocial support material. Secondly, focus groups were convened and facilitated using "we-ness" cards. The quantitative findings demonstrated that the mean score for the perception of social support received by individuals increased. Participants are able to recognise emotions and comprehend when they require different types of support from others, which was a qualitative finding. Participants develop an understanding of their own needs and provide psychological support to others for ensuring optimal well-being in the long term. Further research is required to ascertain the efficacy of the "we-ness" card in a range of community service contexts, particularly those most in need, it is imperative that diverse groups collaborate.